Efforts to Improve Agility in Physical Fitness Activities Through Traditional Boy-Boyan Games for Grade 4 at SDN Babatan IV Surabaya - Faizal Aziz Dirgantara; Sapto Wibowo; Christof Adventa (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
The facts in the field show that there are still many students who are lazy about doing movement activities to achieve physical fitness; therefore, researchers modified this learning in a traditional game to find out how much agility increases in physical fitness activities. The purpose of this study was to determine the increase in agility in physical fitness activities through traditional boy-boyan games in grade 4 at SDN Babatan IV Surabaya. The method used in this research is classroom action research (PTK). This research was conducted using two cycles and began with a pre-cycle, or initial observation. The results showed that there was an increase in learning conducted over two cycles. The results of cycle 1 show that student agility is still in the moderate category with a result of 64.28%, compared to the good category with a result of 35.71%. This percentage has not yet reached the desired achievement indicator and will continue in cycle 2. A significant increase occurred in cycle 2 through learning activities using traditional boy-boy games, which reached 82.14% of the good category. From the results of cycle 2, it has been shown that the success indicator was set at 75%.